2016
DOI: 10.1111/plb.12510
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions are mediated in a sex‐specific manner by arbuscular mycorrhiza in Antennaria dioica

Abstract: ABSTRACT• Plants usually interact with other plants, and the outcome of such interaction ranges from facilitation to competition depending on the identity of the plants, including their sexual expression. Arbuscular mycorrhizal (AM) fungi have been shown to modify competitive interactions in plants. However, few studies have evaluated how AM fungi influence plant intraspecific and interspecific interactions in dioecious species.• The competitive abilities of female and male plants of Antennaria dioica were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The discrepancy between mycorrhizal colonization and B. nana growth is surprising, because especially ectomycorrhizal associations have been found to generally benefit conspecific plants (Bennett et al, 2017). However, the role of mycorrhizas has increasingly been shown to vary from mutualistic to parasitic, depending on the abiotic and biotic context (Johnson & Graham, 2013;Varga, Vega-Frutis, & Kytöviita, 2017). Moreover, the beneficial effect of mycorrhiza is not always correlated with level of root colonization (Treseder, 2013), and mycorrhiza also influence plants in ways unrelated to the nutrient uptake, for example influencing water uptake or disease resistance (Delavaux et al, 2017).…”
Section: Biotic Plant-soil Feedbacksmentioning
confidence: 99%
“…The discrepancy between mycorrhizal colonization and B. nana growth is surprising, because especially ectomycorrhizal associations have been found to generally benefit conspecific plants (Bennett et al, 2017). However, the role of mycorrhizas has increasingly been shown to vary from mutualistic to parasitic, depending on the abiotic and biotic context (Johnson & Graham, 2013;Varga, Vega-Frutis, & Kytöviita, 2017). Moreover, the beneficial effect of mycorrhiza is not always correlated with level of root colonization (Treseder, 2013), and mycorrhiza also influence plants in ways unrelated to the nutrient uptake, for example influencing water uptake or disease resistance (Delavaux et al, 2017).…”
Section: Biotic Plant-soil Feedbacksmentioning
confidence: 99%
“…Studies have reported that AM fungi can improve water-absorbing and nutrient uptake abilities ( Pfetffer and Bloss, 1988 ; Hodge et al, 2001 ; Wu and Xia, 2006 ), increase biomass accumulation ( Al-Karaki et al, 2004 ; Mena-Violante et al, 2006 ; van der Heijden et al, 2006 ; Romero-Munar et al, 2017 ), enhance the survival capacity of host plants ( Rosendahl and Rosendahl, 1991 ; Evelin et al, 2009 ), and even be involved in interactions among plants ( Allen et al, 2003 ; Mack and Rudgers, 2008 ; Wagg et al, 2011 ). For example, mycorrhizal infection increased the level of competition for the same resources between Holcus lanatus and Dactylis glomerata ( West, 1996 ), and the composition of AM fungi communities regulated plant interactions and determined the structure of plant communities among Lotus corniculatus , Festuca ovina , and Plantago lanceolata ( Scheublin et al, 2007 ). The presence of AM fungi decreased the competitive inequality between Trifolium pratense and Lolium multiflorum by reducing growth suppression ( Wagg et al, 2011 ), and AM fungi increased the negative effects of exotic plant Centaurea maculosa on the native plant Festuca idahoensis and enhanced the ability of C .…”
Section: Introductionmentioning
confidence: 99%
“…cathayana ( Chen et al, 2015a ). Meanwhile, in dioecious plant populations, root systems of female and male individuals are closely connected to a common hyphal network through AM fungi and drain carbon or mineral nutrients from other individuals ( Hart et al, 2003 ; Varga et al, 2017 ). Because there exist sex-specific responses to mycorrhiza in a dioecious species (e.g., Varga and Kytöviita, 2008 , 2010b ; Eppley et al, 2009 ; Rogers and Eppley, 2012 ; Varga, 2013 ), the intersexual interactions between male and female individuals should be affected by AM fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, little is known on patterns of dimorphism in below-ground processes and structures. Considering that sexual dimorphism would be the outcome of below versus above processes (Varga et al, 2017), and allocation to above and below-ground sinks (Harris and Pannell, 2008), studies that will focus on these aspects would be especially useful to make a compelling story of sexual dimorphism in plants under stress.…”
mentioning
confidence: 99%